2000
DOI: 10.1007/s001980070077
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Changes in Bone Mineral During Postpartum Amenorrhea and Lactation

Abstract: To determine the physiologic and habitual factors that may modulate changes in bone mineral density (BMD) postpartum, dual-energy X-ray absorptiometry was performed at the lumbar spine, right femoral neck and dominant distal radius immediately after delivery, after resumption of menses, and 1 year thereafter in a cohort of 41 healthy postpartum Finnish women aged 31.5 (SD 4.6) years. Mean durations of lactation and postpartum amenorrhea (PPA) were 7.7 (3.7) and 5.9 (2.9) months, respectively. After PPA, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Radial bone seemed to recover incompletely, or its recovery took more time than that of the other bone sites. This finding agrees with the results of HolmbergMarttila et al [43], who found systematic bone recovery at the spine and femur but a diffuse response at the radius. In any case, the disproportionately large bone loss from distal radius calls for further studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Radial bone seemed to recover incompletely, or its recovery took more time than that of the other bone sites. This finding agrees with the results of HolmbergMarttila et al [43], who found systematic bone recovery at the spine and femur but a diffuse response at the radius. In any case, the disproportionately large bone loss from distal radius calls for further studies.…”
Section: Discussionsupporting
confidence: 83%
“…During pregnancy the fetus takes calcium from the mother to develop its skeleton, and lactation in conjunction with postpartum amenorrhea may result in a loss of calcium and maternal bone loss. In agreement with earlier results, the postweaning recovery at the femur was not complete until well after 12 months [42][43][44]. The total duration of lactation (one long period or many periods of breastfeeding) was a predictor of radial bone loss.…”
Section: Discussionsupporting
confidence: 78%
“…The duration of breast feeding, might affect the maternal bone mass because it suppresses the hypothalamic-pituitary axis and may result in loss of fetal calcium supply from the mother (Zarate and Canales 1987;Glerean and Plantalech 2000;Holmberg-Marttila et al 2000;Hadji et al 2002). Some studies suggest that breast feeding is not related to the BMD (Kritz-Silverstein et al 1992;Fox et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated based on a previous study of BMD measurement carried out in postpartum women, considering a standard deviation of distal radius equal to 0.044 g/cm 2 [6], an alpha of 5%, and a minimum difference between the observed and true measurements of 0.010 g/ cm 2 . The minimum sample size needed using these parameters was calculated as 74 women [7].…”
Section: Methodsmentioning
confidence: 99%